Atypical cause of apnoea in a neonate born at 29 weeks - Dongara, Ashish R.; Agarwal, Ravi; Chandratre, Saleel (International Journal of Contemporary Pediatrics, 2025)
A 29 weeks gestation, male, weighing 1270 grams was born through a vaginal delivery. He was intubated at birth and received 2 doses of surfactant. He had multiple failed extubation attempts on 1st, 7th, 28th, and 54th day of life on account of recurrent apneic spells. The apneic spells continued well beyond 36-37 weeks post menstrual age. He was noted to have subtle signs like poor suck-swallow, and gag reflex for which a pediatric neurology consult was sought. Detailed assessment revealed signs of bulbar weakness, and facial weakness. Magnetic resonance imaging of the brain showed an exophytic space occupying lesion in the medulla oblongata. Liberal excision biopsy was performed; confirming a definitive diagnosis of neuroepithelial tumor, which was difficult to classify, but had features favoring primitive/embroyonal tumor with focal glial differentiation, which carries a guarded prognosis. The child is presently 2 years old and receiving palliative home care. Apnea/s are frequent events in neonates. They can be attributed to a multitude of causes involving all major systems like cardiac, respiratory, neurological, gastro-intestinal, systemic causes like electrolyte imbalance, sepsis, prematurity etc. Apnea of prematurity is one of the common causes. Physicians should be mindful of the usual pathophysiological course of the apnea of prematurity, and its persistence beyond the usual age, especially in the presence of subtle clinical and radiological signs, should warrant further workup.